EKSTRAKSI RUANG KEMACETAN DI KOTA PADANG (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2019)
This research has aimed to describe areas and roads that are prone to traffic jams, the direction of congestion, sources of congestion, and the pattern of time of occurrence of congestion that occurs along roads in Padang City. This type of research is descriptive. This research has been conducted in the city of Padang. The study population is the entire network prone to traffic jams in the city of Padang, samples have been taken with a purposive technique. When the study was conducted in the morning, afternoon and evening at the location of the prone road to the city of Padang. Data analysis techniques that have been done by observation, documentation. It was found that there are 3 road segments prone to traffic jams. Direction of traffic jam Prof. Dr. Hamka experiences traffic jams in the morning in the direction of Pasar Raya, then in the afternoon and in the afternoon it is jammed in the direction of Tabing, Jalan Muhammad Yamin in the direction of traffic jams in Pasar Raya and Jalan Raya Indarung in the direction of Pasar Raya. Road traffic source Prof. Dr. Hamka is caused by the activity of the shadow terminal and the meeting of three currents, on Jalan Muhammad Yamin caused by the market and on Jalan Indarung because of the shadow terminal. In the traffic jam Prof. Dr. Hamka morning and evening, Jalan Muhammad Yamin afternoon and evening and Jalan Raya Indarung morning and evening.